Drug Levels Associated With Optimal Discrimination Between Remission and Nonremission and Comparison of Antibody Assays During First Year of Stable Infliximab Maintenance Therapy in Inflammatory Bowel Disease. Issue 2 (April 2022) - Dorn-Rasmussen, Maria; Buhl, Sine; Brynskov, Jørn; Bay, Jakob T.; Bolstad, Nils; Klausen, Tobias W.; Warren, David J.; Ainsworth, Mark A.; Steenholdt, Casper
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: To implement therapeutic drug monitoring–based strategies for infliximab (IFX) in inflammatory bowel disease, the authors assessed IFX levels for optimal discrimination between remission and nonremission and compared assays for anti-IFX antibodies (Abs). Methods: The retrospective cohort comprised 163 bionaive patients with inflammatory bowel disease who received stable IFX maintenance therapy (5 mg/kg every 8 weeks [q8w]) for 1 year. The clinical and biochemical remission status was assessed at all infusions (weeks 14-22-30-38-46-54), and IFX and anti-IFX Abs were estimated using a time-resolved fluorometric assay (n = 690; 88% of infusions). Samples positive for anti-IFX Abs or IFX levels < limit of detection (n = 102) were analyzed by 2 binding assays [enzyme-linked immunosorbent assay (ELISA)] and functional reporter gene assay/drug-tolerant enzyme immunoassay. Results: At all assessed time points, IFX levels were more than double in patients presenting clinical or biochemical remission. An IFX concentration of 4.5 mcg/mL was associated with clinical remission during the entire first year of therapy [sensitivity 54% (49–59), specificity 73% (67–78), AUCROC 0.65 (0.60–0.69), P < 0.0001]; these values were comparable with biochemical remission. Exploratory assessments for endoscopic remission (n = 131) were performed at the discretion of the treating physician. Anti-IFX Abs were associated with undetectable IFX and treatment failure [OR 2.9 (1.4–6.0), P < 0.01], irrespective of persistency or transiency. All performed assays detected anti-IFX Abs were picked up by all assays in ∼2/3 of samples. Binding assays demonstrated a higher sensitivity to anti-IFX Abs. Conclusions: IFX at ∼5 mcg/mL was associated with clinical and biochemical remission during the first year of maintenance therapy. During this phase of therapy, standard binding assays are appropriate for therapeutic drug monitoring.